PERAN UNITED NATION INTER AGENCY PROJECT ON HUMAN TRAFFICKING DALAM MENANGANI HUMAN TRAFFICKING DI THAILAND - Neli Agustiana; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
UNIAP is an international organization under the United Nations that focuses on Nations that focuses on human trafficking with six membership countries such us Thailand, Myanmar, Cambodia, Laos, Vietnam and China. UNIAP is an inter-agency project of the United Nations (the only agency in the UN system that focuses on human trafficking). This research is based on the theory of the role of international organizations according to Clive Archer, which contains the role of international organizations as arenas, instruments and actors. The data was collected using a qualitative methodology, most of the data published by the official website of UNIAP, the Government of Thailand, books and journals related to human trafficking in Thailand. The results of this study indicate that UNIAP plays a role in overcoming human trafficking in Thailand. First, as an arena in various ethics training activities, media, as well as training on handling human trafficking cases. Second, as an instrument to establish cooperation with COMMIT to produce a Memorandum of Understanding in six UNIAP members on October 29, 2004. Third, as an actor, in carrying out educational programs for children in Thailand in providing education about HIV/AIDS. Fourth, acting as an actor in making hotlines around 10% per month for reports on cases of human trafficking. Fifth, acting as an actor who collaborates with various institutions, in the level of success of UNIAP in establishing 20 international and regional partners, while in the level of failure, UNIAP runs three collaborators with various partners. Keywords: Human Trafficking, Exploitation, Thailand.